Accentuation of Byzantine Greek Inscriptions on Metallic Objects from Different Collections - Аlexandra Evdokimova (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2023)
Introduction. Analysis of sphragistic material in comparison with inscriptions from Italy made on metal showed that in inscriptions of this kind, in addition to the previously known Byzantine, Alexandrian and logical accentuation systems, systems with accent shifts to the right or left were actively used. Methodology. Inscriptions on metal objects were examined on the basis of photographs presented in different editions of the same monument. Material. The article presents the result of an analysis of the use of accentuation marks in 22 Byzantine Greek inscriptions on metal objects of the 9th – 14th centuries, most of which were written in dodecasyllables. Analysis. Inscriptions on metal reliquaries, icon frames, crosses, as well as inscriptions on enamels and encolpions made using various metalworking techniques were analyzed. The elements of Greek accentuation systems presented in them and the directions of stress shifts are described. Results. All presented inscriptions can be divided into two groups: 1) the Byzantine accentuation system with shifts of stress to the right or left with the latter falling between a vowel and a consonant, which can be considered a paleographic feature, as well as the use of trema in cases not determined by phonetic aspects; 2) elements of the Alexandrian system: stress on the unstressed syllable, stress on the first part of the diphthong. In both groups, logical stress could also be placed, including on abbreviations.